Understanding Manufacturing Location Decision Making: Rationales for Retaining, Offshoring, Reshoring, and Hybrid Approaches. Issue 4 (November 2018) - Theyel, Gregory; Hofmann, Kay; Gregory, Mike
How do companies decide where to locate their manufacturing? This study uses insights from manufacturing company executives collected by means of in-depth interviews with 50 manufacturers in the United Kingdom to develop an understanding of manufacturing location decision making. The findings indicate that companies derive competitive advantage from organizing manufacturing in different ways. Retaining or reshoring manufacturing to a company's home country can enhance new product development, control of quality, product customization, delivery performance, and cost leadership. On the other hand, companies can enhance new product development, customization, and delivery performance for new markets, if production facilities are offshored to or in proximity to these locations. In addition, some companies use a hybrid approach of offshoring the production of some components or products for cost arbitrage while retaining or reshoring other components or products for advantages from value chain integration. Based on the findings of this study, a set of key manufacturing location questions are developed that should be considered by firms pondering onshore, offshore, reshore, or hybrid manufacturing location decisions.